Comparative Effects of Ripe and Unripe Lime (Citrus aurantifolia) on Spermatozoa and Gonadosomatic Index in Matured Male Wistar Rats - Ogbonnaya, Obioma; Nwankwo, Azubuike; Ifenkwe, Daniel Chidi; Ibe, Chikera Samuel; Ikpegbu, Ekele; Onwuka, Osah Martins (Biology, Medicine, & Natural Product Chemistry, 2024)
To ascertain the comparative effects of ripe and unripe Lime (Citrus aurantifolia) on spermatozoa and gonadosomatic index evaluation in matured male Wistar rats; exploring the idea that both ripe and unripe Lime (Citrus aurantifolia) might or might not positively affect semen quality, crucial for male fertility. Twenty-eight (28) sexually mature male Wister rats, aged 9–10 weeks and weighing between 211.50g and 217.00g, were divided equally into seven groups (1 to 7); with Group 1 serving as the control and Groups 2 to 7 receiving 25%, 50%, and 75% concentrations of ripe lime juice (RLJ) and unripe lime juice (ULJ) respectively. The findings indicated that ULJ had a higher concentration (0.1mg/ml) compared to ripe lime RLJ at 0.08mg/ml, although both had approximately the same LD50 value of 1581.138mg/kg. RLJ, at different concentrations, adversely impacted the reproductive performance of rats, leading to decreased progressive motility, livability, sperm count, testicular size, and sexual drive. However, ULJ did not exhibit these effects. A 75% concentration of RLJ showed anti-prostatic activity, causing a reduction in prostate size, which was more pronounced than that of the same ULJ concentration. Importantly, both RLJ and ULJ did not have a significant impact on the sizes of the liver, spleen, heart, kidneys, and lungs, with these visceral organs maintaining normal sizes comparable to the control group (statistically, p>0.05).The findings suggest that RLJ or ULJ consumption, particularly at the highest concentration, may lead to alterations in reproductive performance, hence such consumption should be discouraged.